A Review of the Relationship Between EFL Teachers’ Academic Buoyancy, Ambiguity Tolerance, and Hopelessness - Huang, Shuyun (Frontiers in Psychology, 2022)
Second/foreign language education has been approved emotionally-tense due to its inherent challenges, adversities, complications, and ambiguities. These factors can affect various language teaching and learning domains. Hence, it is critical for EFL teachers to be buoyant and tolerant of ambiguity so that they can teach efficiently and prevent a sense of hopelessness that can damage everything. Although there are investigations on these variables in L2 contexts, their main focus has been on EFL students and teachers’ perspectives have been largely ignored. Against this shortcoming, this study aimed to review the definitions, conceptualizations, and research findings related to teachers’ academic buoyancy, ambiguity tolerance, and hopelessness. Moreover, practical implications for EFL teachers and teacher trainers are presented to increase their awareness of language teaching challenges and ways to overcome them. Finally, the study provides directions for future research.